ANALISIS BENTUK DAN RAGAM HIAS PADA MAKAM RAJA TANETE DI KECAMATAN TANETE RILAU KABUPATEN BARRU PROVINSI SULAWESI SELATAN - Fiqih Wulandari; Syahrun Syahrun; sandy suseno (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2020)
ABSTRAct Tombs of Petta Pallase-lase’e and Datu We Tenri Olle are an object of archaeological heritage in the Tanete region, based on are shapes of the two tombs are very unique and contains hostorical elements of cultural and religious developments in Tanete region. The purpose of this study was to determine the shape and variety of the king’s tomb of Tanete, and to find aut cultural elements that influenced it. The research method used is descriptive analytical consisting of several stages, observational, interviews and documentations. The result showed that the shape of the king’s tomb of Petta Pallase-lase’e is stepped pyramid and the shape of the Datu We Tenri Olle’s tombs is dome. In addition there are also decorative arts, namely architectural, and decorative, motive are geometric motives, flora, and inscriptions. Through the shape and variety of the two tombs that element of tombs was influenced by Megalithic, Local, Hindu-Buddha, Islamic, and Colonial cultures that developed in the Tanete region. Keywords: king’s of tomb; shape and decorative; cultural element